Freedom of expression and the phenomenon of “Fake News” in Brazilian law - Jesus, Welder Bezerra de (2024)
The general objective of this study was to analyze the impact of fake news on the exercise of freedom of expression in favor of the challenge of balancing the protection of freedom of expression with the need to combat the dissemination of false information that has legal, social and democratic implications. To this end, as a methodological aspect, a qualitative approach was used, implemented by bibliographical research and documentary analysis. Firstly, we sought to address concepts relating to freedom of expression and the phenomenon of fake news. This right to freedom of expression is a central institute for guaranteeing democracy, oversight of powers and social development. Furthermore, as a fundamental right provided for in art. 5th, IV, of the Federal Constitution of 1988, although there is no absolute fundamental right, it ensures, among others, the fundamental rights to expression of thought, preservation of honor, privacy and public security. Diametrically, there is the propagation of fake news, synthetically conceptualized as the proliferation of false information with a strong potential to denigrate institutions and fragment the social fabric, currently enabled by the growth of digital technologies and social networks, which have transformed the mode of dissemination and/or or dissemination of information. This information dynamic is a legal challenge, as it calls into question the limit between freedom of expression and the fight against disinformation, thus justifying the relevance of this research to the academic field, as it enables the study of the field of Constitutional Law as well as of Digital Law and also addresses social dynamics that affect democratic stability and adequate coexistence in society. As a result, legislative and jurisdictional actions were identified with great relevance in the 2018 and 2022 electoral periods, as well as during the COVID-19 pandemic. In the legislative field, although there is a civil law on the internet, it was found that the legislation lacks a clear and robust approach to adequately hold those involved accountable, including digital platforms, and also guarantee the protection of fundamental rights without the means of protection turn into prior censorship of freedom of expression. In the judicial field, the actions of the STF and TSE made it possible to combat misinformation, especially during the electoral period. However, improvements are necessary to provide adequate media education to citizens for their development in skills that allow them to have a critical view of the information consumed, culminating in the strengthening of democratic institutions.